Heavy oil recovery by surface modified silica nanoparticle/HPAM nanofluids. (15th September 2019) - Corredor, Laura M.; Aliabadian, Ehsan; Husein, Maen; Chen, Zhangxin; Maini, Brij; Sundararaj, Uttandaraman
Highlights: The surface of SiO2 NPs was modified by chemical grafting of octyltriethoxysilane, oleic acid and stearic acid. HPAM improved the colloidal stability of all NPs and reduced the size of the NP aggregates. The intra-cycle shear-thickening behavior of the polymer solution severely decreased with incorporation of all SiO2 NPs. The addition of 0.2 wt% SiO2 -OTES nanoparticles increased the cumulative oil recovery of HPAM solution. Abstract: Recent studies showed that the presence of dispersed nanoparticles (NPs) can increase the efficiency of polymer flooding. The network structure of polymer/NP hybrid dispersion has a significant impact on oil recovery. In this work, the surface of SiO2 NPs was modified by chemical grafting of octyltriethoxysilane (SiO2 -OTES), oleic acid (SiO2 -OAA) and stearic acid (SiO2 -SAA) in an attempt to stimulate higher degree of interaction with partially hydrolyzed polyacrylamide (HPAM). Thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and Fourier transform infrared (FTIR) spectroscopy were employed to characterize the modified silica NPs. In addition, ζ-potential, cryo-scanning electron microscopy (cryo-SEM), and linear and nonlinear rheology were used to evaluate the characteristics of the hybrid dispersion of HPAM/unmodified and modified SiO2 NPs. ζ-potential measurements showed that the addition of HPAM improved the colloidal stability of the modified and unmodified SiO2 NPs dispersed in deionized (DI) water. Moreover, the addition of HPAM reduced the size of the NP aggregates by effective steric repulsion. Small and large shear oscillatory deformation results showed that SiO2 -OTES NPs improved the HPAM network significantly. Nevertheless, HPAM/NPs network formed with all the different SiO2 NPs severely decreased the intra-cycle shear-thickening behavior of the polymer. Lastly, the addition of 0.2 wt% SiO2 -OTES NPs to the HPAM solution increased the ultimate oil recovery from 71.4% to 75.7% OOIP.